Prevalence of Atopy in 1,199 Asthmatic Children from Southern Santiago, Chile [Prevalencia y Perfil de Sensibilización a Aeroalérgenos en 1.199 Niños Asmáticos: Serie Consecutiva de Casos] - Mallol-Villablanca, E; Raby-Amadori, P (Sociedad Medica de Santiago, 2014)
Background: The prevalence of atopy in asthmatic children is widely variable around the world as demonstrated by large multicentric international studies. Aim: To determine the prevalence of atopy, defined as a positive reaction to one or more allergens in the skin prick test (SPT), in children with persistent asthma. Material and Methods: We studied 1,199 children (54% male), aged between 4 and 16 years with confirmed diagnosis of asthma and followed at a Department of Pediatric Respiratory Medicine, between 2006 and 2011. SPT was performed according to international recommendations using standardized aeroallergens, in the forearm. A positive reaction was defined as a wheal ? 3 mm to one or more allergens. Results: The overall prevalence of atopy (positive SPT) was 49.4% (95% confidence interval (CI) 46.5-52.2) and there was a significant trend towards a higher prevalence with increasing age (p < 0.01). The main allergens with positive reactions were Dermatophagoides with 24.9% (95% CI 26.7-31.9), grass 24.0% (95% CI 21.6-26.5), weeds 19.0% (95% CI 16.9-21.4), cat 17.7% (95% CI 15.4-20.2), and Alternaria with 11.0% (95% CI 9.1-13.1). Sixty five percent of positive children reacted to one or more allergens. There were no adverse reactions. Conclusions: In the southern metropolitan area of Santiago de Chile, half of children with asthma are sensitized to common aeroallergens.
Keywords: Asthma; Child; Epidemiology; Hypersensitivity